2021
DOI: 10.1093/narcan/zcab025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression and mutation data points on contribution of transcription to the mutagenesis by APOBEC enzymes

Abstract: Since the discovery of the role of the APOBEC enzymes in human cancers, the mechanisms of this type of mutagenesis remain little understood. Theoretically, targeting of single-stranded DNA by the APOBEC enzymes could occur during cellular processes leading to the unwinding of DNA double-stranded structure. Some evidence points to the importance of replication in the APOBEC mutagenesis, while the role of transcription is still underexplored. Here, we analyzed gene expression and whole genome sequencing data fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Whereas experimental analyses will be necessary to determine the source of APOBEC3-mediated editing in hMPXV1 genomes and the nature of repair mechanisms (or lack thereof), we found that mutations are more common in highly expressed genes. A similar observation was recently reported for some cancer genomes ( 11 ), explained by the fact that transcription leads to dsDNA unwinding, with the transient formation of single-stranded DNA (ssDNA) regions, a target of APOBEC3-mediated editing. The same authors also reported transcriptional asymmetry of APOBEC3 mutation signatures, a feature we do not observe in hMPXV1 genes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Whereas experimental analyses will be necessary to determine the source of APOBEC3-mediated editing in hMPXV1 genomes and the nature of repair mechanisms (or lack thereof), we found that mutations are more common in highly expressed genes. A similar observation was recently reported for some cancer genomes ( 11 ), explained by the fact that transcription leads to dsDNA unwinding, with the transient formation of single-stranded DNA (ssDNA) regions, a target of APOBEC3-mediated editing. The same authors also reported transcriptional asymmetry of APOBEC3 mutation signatures, a feature we do not observe in hMPXV1 genes.…”
Section: Discussionsupporting
confidence: 79%
“…APOBEC3 proteins have been intensely investigated for their mutagenic role in human cancers. In cancer genomes, there is contrasting evidence for transcriptional asymmetry of APOBEC3-induced mutations ( 10 12 ). Replication asymmetry is instead observed, with most mutations occurring on the lagging strand ( 10 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several types of mutational heterogeneity along the genome, presumably associated with replication and transcription ( Haradhvala et al., 2016 ), were identified for APOBEC mutagenesis. An increased density of APOBEC-induced mutations was found in early-replicating genome regions ( Kazanov et al., 2015 ), as opposed to other types of cancer mutagenesis, and in highly transcribed genes ( Chervova et al., 2021 ). Higher rate of APOBEC-induced mutations was also observed on the lagging replicating DNA strand ( Seplyarskiy et al., 2016 ) and the non-transcribed DNA strand ( Chervova et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%